Methylamine gas healing of perovskite films: a short review and perspective. Issue 7 (22nd November 2021) - Hao, Lianzheng; Zhao, Qiangqiang; Wang, Xiao; Pang, Shuping; Cui, Guanglei
Abstract : We summarize the internal chemical mechanism, crystallization kinetics and future prospects of the MA 0 healing process. Abstract : The first challenge in the commercialization of perovskite solar cells (PSCs) is how to easily fabricate large-scale, high-quality perovskite films. Although some methods have been developed for the fabrication of large-scale films, the film quality still needs to be improved. The MA 0 healing method, as a post-processing technique, can be perfectly combined with other large-scale methods. However, determining the mechanism of the whole process is crucial for commercial production and subsequent research. Herein, we summarize the research progress on the MA 0 healing method. Firstly, we introduce the interaction during the liquification process including the interaction of amines with Pb 2+, the generation of hydrogen bonds, the influence of H2 O, and the reactions between different amines. Then, we systematically discuss the dynamic mechanism of adsorption and desorption. Finally, several aspects that need to be further clarified are proposed.